Penguatan Nilai Ideologi Pacasila Dan Wawasan Kebangsaan Terhadap Masyarakat Wujud Mempertahankan Budaya Bangsa - Idham; Sudewi Sudewi; M. Fikri Akbar; Lenny Nadriana (JURNAL ABDIMAS DOSMA (JAD), 2025)
Many of the analysis of figures in various discussions and research that show several trends in the depletion of the spirit of nationalism among the younger generation among the younger generation, including the general public. At the same time, the development of nationalism through the role of institutional units outside the world of education, for example the conducted by the Bandar Lampung City Council with the theme “Socialization of the ideology of Pancasila and Nationalistic Insight” in various discussions and researches. Pancasila and Nationalistic Insight” in several theoretical studies provide a significant contribution. significant contribution. Therefore, making an institutional unit outside of education as a location for service as an endeavor to shape and develop national character (nationalism) is the right answer in preparing the younger generation and the community to become quality human resources who are able to be wise in responding to globalization. globalization. The objectives of this community service activity are the formation of strengthening Nationalism values that grow from awareness and knowledge in the community. awareness and knowledge in the community. Methods used used by the Service Team is socialization, counseling, and coaching so that the community has comprehensive knowledge about nationalism, measuring the nationalism index, and measuring the nationalism index. have comprehensive knowledge about nationalism, measurement of nationalism index, as well as index, as well as nationalism character statutes and being able to behave well in protecting the country. well in maintaining the Unitary State of the Republic of Indonesia. Unitary Republic of Indonesia.